2014
DOI: 10.1371/journal.pone.0092083
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Seven Common Polymorphisms from Five DNA Repair Genes and the Risk for Breast Cancer in Northern Chinese Women

Abstract: BackgroundConverging evidence supports the central role of DNA damage in progression to breast cancer. We therefore in this study aimed to assess the potential interactions of seven common polymorphisms from five DNA repair genes (XRCC1, XRCC2, XRCC3, XPA and APEX1) in association with breast cancer among Han Chinese women.Methodology/Principal FindingsThis was a case-control study involving 606 patients diagnosed with sporadic breast cancer and 633 age- and ethnicity-matched cancer-free controls. The polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…It has been suggested that mutations in XRCC1, XRCC2 and XRCC3 genes may contribute to decreased or lost DNA repair capacity. Furthermore, SNP of XRCC1, XRCC2 and XRCC3 may affect the risk of several types of cancer, including thyroid carcinoma, glioma and breast cancer [21,28,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that mutations in XRCC1, XRCC2 and XRCC3 genes may contribute to decreased or lost DNA repair capacity. Furthermore, SNP of XRCC1, XRCC2 and XRCC3 may affect the risk of several types of cancer, including thyroid carcinoma, glioma and breast cancer [21,28,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, there is significant evidence showing that these three genes are involve in modulating the pathway in the development of breast cancer. Single nucleotide polymorphisms (SNPs) in CYP2E1 (rs6413432 and rs3813867), STK15 (rs2273535 and rs1047972) and XRCC1 (rs1799782 and rs25487) were inconclusively associated to breast cancer risk in case-control or meta-analysis studies in different populations (Wu et al, 2006;Bu et al, 2014;Dai et al, 2014;Ding et al, 2014;Feng et al, 2014;Guo et al, 2014;Qin et al, 2015), but association of these SNPs to breast cancer in Southeast Asia populations, especially in Malaysian women was unquestionably insufficient. Therefore, this pilot study investigates the association of these SNPs, together with etiology factors such as age and ethnicity, to breast cancer risk in Malaysian women.…”
Section: Introductionmentioning
confidence: 99%
“…XRCC2 has been explored and determined to play some roles in various types of human tumors, including breast cancer, thyroid cancer, pancreatic cancer and other types of carcinomas [30, 36-41]. Low levels of XRCC2 have been detected in breast cancer [42], whereas greater XRCC2 expression is present in rectal cancer and gastric cancer [30, 43]. It has been hypothesized that XRCC2 expression is related to the initiation or progression of carcinogenesis [44].…”
Section: Discussionmentioning
confidence: 99%